Legba - Hirtt, Sarah (Belgium, 2011)
Between spirituality and exile, commitment and transmission, the film sketches the portrait of a Haitian woman living in Montreal. Like the voodoo spirit "Legba", it opens the border.
Verzio Film Festival Submission
Keywords: Documentary films